Consolidation of Ultrasound and Light: Silicon Phthalocyanine-Based Sensitizer Therapeutic Agent for Synergetic Sonodynamic-Photodynamic Therapy of Breast Cancer - Cakmak, Hilal; Turkkol, Aysegul; Kolac, Umut Kerem; Atmaca, Goknur Yasa; Kuznetsov, Aleksey E.; Cavus, M. Serdar; Yildiz, Mustafa Z.; Sobotta, Lukasz; Bilgin, Mehmet Dincer; Erdogmus, Ali; Guzel, Emre (WILEY-V C H VERLAG GMBH, 2025)
Sono-photodynamic therapy (SPDT), a useful technique applied in combination with photodynamic therapy (PDT) and sonodynamic therapy (SDT), reduces potential side effects compared to monotherapy. This study reports the photochemical and sono-photochemical properties and in vitro analysis of silicon (IV) phthalocyanine (SiPc), with a particular focus on its efficiency in singlet oxygen production. When photochemical investigations are conducted alone, the SiPc Phi triangle value is measured as 0.68; however, when light and ultrasound are combined, the value increased by 25% to 0.85 in sono-photochemical studies. The Q-band of the calculated SiPc UV-vis spectrum is found to be in very good agreement with the experimental data, with the computed oscillator strengths (the absorption intensities) for Q-band being higher than for B-band. Furthermore, the therapeutic effects of PDT and SPDT using SiPc are evaluated in MCF-7 and MDA-MB-231 breast cancer cell lines. The results demonstrated that SPDT, combining light and ultrasound, significantly enhanced cytotoxicity compared to PDT alone. Additionally, SPDT triggered pyroptosis, characterized by upregulation of NLRP3, CASP1, IL1B, and IL18, revealing a distinct mechanism of cell death. These findings suggest that SiPc-mediated SPDT amplifies oxidative stress and activates multiple cell death pathways, offering a promising and targeted approach for improving breast cancer therapy.
Keywords: breast cancer; photodynamic therapy; phthalocyanine; sensitizer; silicon; sonodynamic therapy; PHOTOSENSITIZERS; Pharmacology & Pharmacy